A Modified MAP Turbo Decoding Algorithm - Rogeau-Azizi, L. (2006 International Symposium on Communications and Information Technologies : Bangkok, Thailand, 18-29 October 2006, 2006)
In this paper, an improved maximum a posteriori probability (MAP) turbo decoding algorithm is proposed. This algorithm reduces the computational complexity however is exactly equivalent to the MAP turbo decoding. Then we extend the new algorithm for log-MAP. We also present some complexity comparison to show that the modified algorithm requires fewer computation than MAP. As a practical example forming the basis for simulations, we consider a parallel concatenated trellis-coded modulation (PCTCM). The simulation results prove that our simplified algorithm is equivalent to the log-MAP algorithm in term of the performance